Hubungan Life Style (Kebiasaan Makan dan Aktivitas Fisik) dengan Kejadian Diabetes Melitus di Wilayah Kerja Puskesmas Pampang Kota Makassar - Syaipuddin, Syaipuddin; Suhartatik, Suhartatik; Haskas, Yasir; Nurbaya, Sitti (Bunda Edu-Midwifery Journal (BEMJ), 2024)
Changes in social structure from agrarian to industrial societies contribute significantly to lifestyle changes and can lead to an increase in non-communicable diseases such as diabetes mellitus (DM). This lifestyle includes diet and physical activity. Unhealthy eating habits and lack of physical activity are one of the triggers for DM. The purpose of this study is to determine the relationship between lifestyle (diet and physical activity) and the incidence of type 2 diabetes mellitus at the Pampang Health Center, Makassar City. The research design of the correlation descriptive approach uses a cross-sectional approach. The population of this study only consists of outpatients who are diagnosed with diabetes at the Pampang Health Center, Makassar City. Sampling was carried out through purposive sampling, the sample of this study amounted to 60 people, and the collection technique was purposive sampling technique. Purposive Sampling data uses a questionnaire. The statistical test used is chi-square. Based on the research that has been conducted, the results were obtained that there is a relationship between diet and the incidence of DM (p=0.02<α=0.05) and there is a relationship between physical activity and the incidence of DM (p=0.009<α=0.05). = 0.05). The results of this study concluded that there was a relationship between lifestyle (eating habits and physical activity) and the incidence of type 2 diabetes mellitus at the Pampang Health Center, Makassar City. Therefore, it is recommended that health workers pay more attention to the diet of the DM patients they treat, and DM patients regulate their eating habits and maximize physical activity